Bridging A Continent : Aldus Encyclopedia of Discovery and Exploration - Hillman, Martin (London; Aldus Books, 1971)
The history of colonizing North America and Native Americans.
1. The Spirit of Expansion, 2. Forerunners, 3. Corps of Discovery, 4. Edging Toward the Southwest, 5. Fur Traders and Mountain Men, 6. The Road to Santa Fe, 7. Reaching for California, 8. The Pathfinder, 9. The Fact Finders, 10. The Disinherited, 11. The Inheritors.
English
Keywords: 18th century; G200-336 Geography (General)- History of discoveries, explorations, and travel